Air Quality Monitoring and Purification Devices: A Review (International Journal of Innovative Research in Computer Science & Technology, 2020)
Air quality has been degrading due to  increase in vehicles and industrial activities. These  industrial activities and vehicles cause most of the air  pollutants as gases, but some are very tiny solid particles,  such as dust, smoke. Most commonly detected air  pollutants are Sulphur Dioxide (SO2), particulate matter,  Hydrocarbons (HC), Lead, Carbon Dioxide (CO2) and  Carbon Monoxide (CO), Nitrogen Oxides (NOx), and  smog. These air pollutants affect both the indoor and  outdoor air. The indoor air is more polluted, due to the  release of the air borne chemicals while cooking and  from furniture. The polluted air is unsafe for human  health. So, the need of an indoor automatic air purifier  arises. This paper presents a thorough study of different  techniques and models developed to monitor the air  quality and hereby control the air purifier system.
Keywords: Pollution; indoor air; purifier; air quality